The Failing Right Heart - Anastasiadis, Kyriakos; Westaby, Stephen; Antonitsis, Polychronis; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book provides an up-to-date and comprehensive overview of the etiology, diagnosis, and treatment of conditions affecting the structure and function of the right heart, comprising the right atrium, right ventricle, tricuspid valve, and pulmonary circulation. The right ventricle works against a reduced afterload as compared to the left ventricle, and the clinical picture of heart failure is generally dominated by the symptoms of left heart failure and hence initially neglected until they evolve into overt right heart failure with splanchnic congestion. When picked up at the very late stage, medical management and mechanical support of right heart failure are considered ineffective, and heart transplantation offers the only treatment option. The Failing Right Heart will be an essential reference for cardiac surgeons, cardiologists, cardiac anesthesiologists and cardiac intensivists on the diagnosis and treatment of patients with congenital or acquired right heart disease. The book deals with anatomy and physiology of the right heart, the etiology and the role of imaging of right heart failure, as well as the treatment options, from pharmacological regimes to surgery. Algorithms and flow diagrams are included to provide the reader with illustrated snapshots of the decisions involved in the management of these patients.
Introduction -- Anatomy of the failing right heart -- Physiology of the failing right heart -- Pharmacologic approach to the failing right heart -- Echocardiographic evaluation of right heart failure -- Right heart catheterization for the failing right heart -- Magnetic Resonance Imaging of the failing right heart -- The failing right heart in congenital diseases -- Surgery of the tricuspid valve in right heart failure -- Pulmonary embolism and right heart failure -- Anaesthetic consideration and perioperative management in right heart failure -- Mechanical support and the right heart -- Special considerations.
Keywords: Cardiology; Cardiac surgery; Cardiology; Cardiac Surgery